Jones matrix‐based speckle‐decorrelation angiography using polarization‐sensitive optical coherence tomography. Issue 9 (23rd June 2020) - Gong, Peijun; Li, Qingyun; Wang, Qiang; Karnowski, Karol; Sampson, David D.
Abstract: We show that polarization‐sensitive optical coherence tomography angiography (PS‐OCTA) based on full Jones matrix assessment of speckle decorrelation offers improved contrast and depth of vessel imaging over conventional OCTA. We determine how best to combine the individual Jones matrix elements and compare the resulting image quality to that of a conventional OCT scanner by co‐locating and imaging the same skin locations with closely matched scanning setups. Vessel projection images from finger and forearm skin demonstrate the benefits of Jones matrix‐based PS‐OCTA. Our study provides a promising starting point and a useful reference for future pre‐clinical and clinical applications of Jones matrix‐based PS‐OCTA. Abstract : This study investigates Jones matrix‐based speckle‐decorrelation polarization‐sensitive optical coherence tomography angiography (PS‐OCTA) imaging by assessing the data processing methods and comparing its image quality to conventional OCTA. Imaging of human finger and forearm skin shows the benefits provided by PS‐OCTA over conventional OCTA, including improved vessel contrast and imaging depth. This study provides a useful reference point for future preclinical and clinical applications of Jones matrix‐based PS‐OCTA.